Coronal repercussions of maxillary central incisor torque with clear aligners – Invisalign system - Oliveira, Ana Catarina; Rocha, Ana Sofia; Sousa-Santos, Primavera; Pinho, Teresa (Scientific Letters, 2024)
Recent years have witnessed a big evolution of clear aligner technology, due to the growing importance of aesthetics and comfort. An adequate coronal torque value has a significant impact on smile aesthetics and on the patient’s soft tissue profile. The aim of this systematic review is to evaluate the current knowledge about the efficacy of the maxillary central incisor coronal torque in the InvisalignÒ system. This study protocol was submitted to the PROSPERO database. Literature research was performed in PubMed, EBSCO Essentials, and Cochrane Library, for articles published from January 2013 to June 2024, using MeSH terms. The literature search identified a total of 281 articles in databases and 3 articles using manual search. Finally, 6 retrospective studies were used for this review work. The ROBINS-I tool was used to assess the methodological quality of the studies. Most studies found significant differences between planned and achieved torque values using the Invisalign® system. A study found that central upper incisor coronal torque was normally underexpressed when the teeth were moving labially and fully or overexpressed when moved lingually.